IoT Soil Moisture Monitoring and Irrigation System Development - Chew, Kim Mey; Syvester Tan, Chiang Wei; Gary Loh, Chee Wyai; Nancy, Bundan; Yiiong, Siew Ping (2020)
Agriculture is vital in human evolution and was the first activity to be emphasized ever since the beginning of time. With the population growing constantly, there are inventions of new means in the production of food to cater for those demands. Improvement in a variety of technologies is one of such effort conducted for the cause. Robotics or chemical technologies may not be the only improvements that could be exercised. Internet of Things (IoT) technology is one of an application widely used currently. The study aims to establish a less manpower plantation in smart city with the use of IoT technology to improve the crop cultivation. In preliminary, a wireless soil moisture monitoring and irrigation system was developed. The system aims to monitor the moisture and properties of soil for plants. At the same time, with a self-sufficient and self-organized irrigation system based on the water-control algorithm. The developed system covered the three layers in IoT architecture: perception layer, network layer and application layer. In perception layer, a microcontroller, soil moisture sensors and solenoid valves acted as the sensors, transducers and actuators. Wireless networking technology (WiFi) was used as the communication for data transmitting and receiving. Through the developed application, humidity and irrigation volume were collected, recorded and analyzed. These preliminary results help in visualizing the concept of a less manpower plantation in smart city.